Motorized spiral enteroscopy-assisted ERCP in surgically altered anatomy: early experience from a retrospective cohort study - Schneider, Markus; Höllerich, Jörg; Gerges, Christian; Balasus, Nicole; Neuhaus, Horst; Beyna, Torsten (Endoscopy, 2023)
Background Motorized spiral enteroscopy (MSE) was recently introduced into clinical practice. The aim of the current study was to evaluate the feasibility and safety of MSE for biliopancreatic interventions in patients with surgically altered anatomy.Methods Patients with surgically altered anatomy receiving MSE-assisted ERCP at a single, endoscopy referral center were retrospectively enrolled between January 2016 and June 2021.Results 36 patients (14 female, 22 male), median age 67 years (range 43–88), with biliary (n = 35) and pancreatic (n = 1) indications for MSE-ERCP, were enrolled. The majority (75.0 %) had relevant comorbidities (American Society of Anesthesiologists class III). Surgical reconstruction included Roux-en-Y (n = 30) and Billroth II (n = 6). Technical success rates for enteroscopy, cannulation, and interventions were 86.1 %, 83.9 %, and 100 %, respectively. The overall MSE-ERCP success rate was 72.2 %. One major complication occurred (2.8 %; delayed post-sphincterotomy bleeding).Conclusions This is the first study to demonstrate the feasibility and safety of MSE-assisted ERCP in postsurgical patients with altered anatomy at an expert center. These data justify further evaluation of this new technique, preferably in a prospective multicenter trial.